Assessing Efficiency of the Financial Sector in Ghana and Implications for Growth: An Application of the Ahiawodzian Model of Financial Market Efficiency - Ahiawodzi, Anthony (International Journal of Economics, 2025)
Purpose: The importance of efficiency of the financial sector in promoting economic growth and development, particularly in developing economies, has been well documented in the economic literature. For example, the McKinnon (1973) and Shaw (1973) theories explicitly state this, with emphasis on developing economies. Therefore, the study set out to empirically assess the efficiency of the financial sector in Ghana from 1988 to 2023, and examine the implications for growth of the Ghanaian economy. Methodology: The study applied a statistical model developed by the author in 2012 known as, the Ahiawodzian Model of Financial Market Efficiency to the financial sector of Ghana from 1988 to 2023. The key variables of the model are the interest rate and inflation rate. The time series properties of the variables of a regression model specified to estimate the long-run real interest rate were carried out. These were the stationarity and cointegration tests to see if the two key variables of the interest rate and inflation rate were non-stationary and cointegrated. The Ordinary Least Squares method was used to estimate the regression model. Findings: The empirical results of the study revealed that the Ghanaian financial sector was inefficient during period 1988 to 2023, even during the financial reform period. The inefficiency level was as high as 51.45%. Thus, the prevailing high level of the financial sector inefficiency in Ghana during the period adversely affected private savings, private investments and economic growth of the country. Unique Contribution to Theory, Practice and Policy: The study therefore recommends to the Ghanaian financial authorities among others; control of the prevailing high inflation rates, effective use of the monetary policy, effective use of the fiscal policy (expenditure rationalisation and revenue mobilisation), reduction of the prevailing high interest rates, reduction of the persistent depreciation of the Cedi in order to reduce the high level of financial sector inefficiency in Ghana, in order to promote economic growth in the country.